The benefit of music education for children development towards social, intelligence, emotion and psychomotor / Muhammad Aiman Mohd Rozimi - Mohd Rozimi, Muhammad Aiman (2023)
This thesis to find the benefit of music education for children development towards social, intelligence, emotion and psychomotor and to explore the usefulness of music education for children. This study only using secondary data for collection data. It only involves children from age 5-12 years old. The study found that music education really helps children to develop their social, intelligence, emotion and psychomotor. This study will benefit to children where it only observes children.